If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 17j + -6 = 14j + 7 Reorder the terms: -6 + 17j = 14j + 7 Reorder the terms: -6 + 17j = 7 + 14j Solving -6 + 17j = 7 + 14j Solving for variable 'j'. Move all terms containing j to the left, all other terms to the right. Add '-14j' to each side of the equation. -6 + 17j + -14j = 7 + 14j + -14j Combine like terms: 17j + -14j = 3j -6 + 3j = 7 + 14j + -14j Combine like terms: 14j + -14j = 0 -6 + 3j = 7 + 0 -6 + 3j = 7 Add '6' to each side of the equation. -6 + 6 + 3j = 7 + 6 Combine like terms: -6 + 6 = 0 0 + 3j = 7 + 6 3j = 7 + 6 Combine like terms: 7 + 6 = 13 3j = 13 Divide each side by '3'. j = 4.333333333 Simplifying j = 4.333333333
| 18.24=-16t^2+24t+8 | | 3n-9=2n+13 | | 8-6n=-7+5(5n+3) | | 7i/8i | | -8x+y=50 | | x-12/5=-6 | | 7-(2-y)=-4 | | 18.24=-16t+24t+8 | | x+39-3x-40=949 | | 9*45=5(f-32) | | (n-12)*8=80 | | x+x+37+4x-40=819 | | 19-5x=7x+19 | | -3y-27=-6(y+6) | | t=(x+y)(2x-y) | | 5*(x-2)=2+2x+x+4 | | 0=5x^2+15 | | 7x-32+3x+12=180 | | -24x=7x-4 | | (n-8)*8=32 | | 10y+8x=210 | | (j+9)(5j+7)=0 | | x^2-15x+68=0 | | 9(2+r)-3(r-1)=33 | | x+2=-36 | | (n-19)*3=12 | | 12*45= | | 60/(-4)x(-9) | | 3n+2=n+10 | | 4x-14=5x-22 | | y=(2x-3)(7-x) | | 12-6(5x-8)-9x=-2(-8x+7)-10 |